2021
DOI: 10.31234/osf.io/8nhej
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antipoverty programs mitigate socioeconomic disparities in hippocampal volume and internalizing problems among U.S. youths

Abstract: Low socioeconomic status (SES) in childhood is associated with altered neural development and elevated risk for psychopathology. Can public policies that increase financial resources for families with low income—including cash assistance programs and the presence of Medicaid expansion—reduce these socioeconomic disparities in brain development and mental health? Addressing this question has not been previously possible, because neuroimaging studies are typically conducted in a single community. We leverage a u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…While it would be premature to base specific policies on our results, future research in this direction could provide insights that can be translated into targeted interventions [see ( 40 ) for an in-depth discussion]. For example, further insights into whether cognitive stimulation during early life or anti-poverty policies ( 13 , 41 , 42 ) reduce neural disparities would be valuable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it would be premature to base specific policies on our results, future research in this direction could provide insights that can be translated into targeted interventions [see ( 40 ) for an in-depth discussion]. For example, further insights into whether cognitive stimulation during early life or anti-poverty policies ( 13 , 41 , 42 ) reduce neural disparities would be valuable.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroscience research on SES has revealed a generally positive relation with overall brain volume, as well as with regional cortical and subcortical volumes and cortical surface areas ( 8 10 ). We note variability across studies in the regions most associated with SES, which may be due, in part, to the relatively small samples studied, to differences in the ways SES has been measured and analyzed (e.g., choices of covariates) ( 10 , 11 ), and to different environments with different levels of assistance to individuals of low SES ( 12 , 13 ). One of the goals of the present study is to establish the relation of SES to regional gray matter volumes (GMVs) in the largest sample so far examined for voxel-level data, using a comprehensive measure of SES and controls for a number of potential confounds, based on a well-powered, preregistered analysis plan.…”
Section: Introductionmentioning
confidence: 98%
“…This issue can be modeled by making inference rates dynamic and heterogeneous, for example, through coupling to agents' socioeconomic status (SES) or age. Importantly, SES has been shown to correlate negatively with the presence of stressors that inhibit the cognitive ability of people to learn [39][40][41], and positively with educational outcomes [42][43][44]. Coupling learning rates to SES would alter the population learning trajectory and potentially attenuate its effectiveness in reducing information and wealth inequality.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the burden of trying to adapt to unfair structural conditions may contribute to chronic stress and increased allostatic load (McEwen & Wingfield, 2003); future research should investigate this possibility. Indeed, there is recent evidence from the ABCD sample that patterns of brain development are associated meaningfully with the implementation of social and economic policies aimed at mitigating resource strain for low SES children, pointing to the importance of focusing efforts on removing structural barriers to children’s success (Weissman et al, 2021).…”
Section: Discussionmentioning
confidence: 99%